âPasien Pandaiâ Program: An Effort to Increase Adherence to Medication In Diabetes Mellitus Type 2 Patients - Dinni, Siti Muthia (Universitas Ahmad Dahlan, 2016)
AbstractÂ Diabetes Mellitus type 2 (DM 2) is a type of chronic disease that is essentially incurable. The only possible effort for health maintenance is self-management to keep blood glucose levels normal. Although adherence to medication arrangements is important for patients, their tendency to comply is relatively low. Having seen this problem, there is a need for a psychological intervention that is focused on the growth of acceptance, strengthens commitment for a change, and facilitates behavioral change. The âPasien PANDAIâ (Patients with Acceptance and Action) Program was designed integratively to accommodate the stated three focuses. A Quasi-Experiment with The One-Group Pretest-Posttest Design was defined as the study design. The subjects of the experiment were five members Persadia (Diabetes Association of Indonesia), Yogyakarta branch. Data Analysis was done with Wilcoxon Signed Rank Test and descriptive analysis. Research results indicate that âPasien PANDAIâ Program cannot increase adherence to medication in DM 2 patients (Z = -1,826 ; p > 0,05) with constant results up until follow-up (Z = -0,535 ; p > 0,05). However, descriptive analysis shows that DM 2 still feels certain benefits from the program.Â Keywords: Program pasien pandai, acceptance, commitment, action, diabetes mellitus, chronic Â disease, adherence to treatment.